Creation of national facilities for the promotion of renewable energies in CIATEQ A.C. - Escamilla-Martínez, Agustín; Hernández-Arriaga, Isaac (Renewable Energy, Biomass & Sustainability, 2021)
The result of 11 years of work for the creation and strengthening of capacities for research and technological development in renewable energies in Mexico, carried out by a Public Research Center, is presented. The project began incipiently in 2010, with a group of 6 mechanical engineers and currently there are a total of 19 people including doctors, master’s degree, and engineers, as well as technical-administrative facilities and laboratories to attend the following research lines: Solar thermal and photovoltaic energy, Wind energy, Bioenergy, Mini-hydroelectric, and Energy efficiency. The growth of the line of work was based on the project execution linked to real needs and the management of various national research funds, which allowed the assimilation of knowledge, the training of human resources, the creation and dissemination of knowledge, the generation of intellectual property and the establishment of strategic alliances. The lines of greatest interest to both the government and the productive sector are in solar thermal energy for the development of hybrid systems in fluid heating, and the wind energy line for the development of medium and low power horizontal axis wind turbines.